Differential Analysis of Hemogram Parameters and Cellular Ratios in Severe Asthma Exacerbations: A Comparative Study of Eosinophilic and Non-Eosinophilic Phenotypes - Nicolae Demenciuc; Corina Eugenia Budin; Corina Ureche; Mircea Stoian; Teodora Nicola-Varo; Dragos-Florin Baba; Dariana-Elena Pătrîntașu; Diana Deleanu (Life)
Asthma exacerbations are acute worsening episodes in individuals with bronchial asthma, frequently necessitating emergency hospital care. Early differentiation between eosinophilic (≥150 eosinophils/mm3) and non-eosinophilic (<150 eosinophils/mm3) subtypes plays a crucial role in treatment decisions and identifying patients eligible for biologic therapies. The ExBA Study explored variations in complete blood count (CBC) parameters and derived cellular ratios—namely the neutrophil-to-lymphocyte (NLR), thrombocyte-to-lymphocyte (TLR), and eosinophil-to-leukocyte ratios (ELR)—in adults hospitalized with severe asthma exacerbations. Ninety patients were enrolled and categorized into eosinophilic (n = 38) and non-eosinophilic (n = 52) groups. Significant statistical differences were observed in the neutrophil and lymphocyte levels, as well as in all three ratios. ROC analysis highlighted the ELR as the most specific indicator of the eosinophilic phenotype (specificity 100%, AUC 0.938, cut-off 0.003), whereas the NLR and TLR showed stronger associations with the non-eosinophilic group (AUC 0.733 and 0.676). No meaningful differences emerged regarding arterial blood gas levels, length of hospital stay, treatment costs, or mortality. A notable association was found between a personal or family history of atopy and the eosinophilic subtype (p = 0.0181). This study underscores the relevance of CBC-based ratios in asthma phenotyping during exacerbation events.